Virus exists in pigs but not same as current strain - New Straits Times (2009)
IT happened in 2004 when the veterinary Services Department undertook a study to check on the prevalence of diseases among pings based on the samples collected during the Nipah outbreak in Peninsular Malaysia in 1990.